Interleukin‐27 signalling induces stem cell antigen‐1 expression in T lymphocytes in vivo. Issue 4 (23rd August 2017) - Liu, Zhihao; Wu, Lisha; Zhu, Jing; Zhu, Xiaotong; Zhu, Jianmin; Liu, Jin‐Qing; Zhang, Jianchao; Davis, Jonathan P.; Varikuti, Sanjay; Satoskar, Abhay R.; Zhou, Jie; Li, Ming‐Song; et al.
Summary: Stem cell antigen‐1 (Sca‐1/Ly6A/E) is a cell surface glycoprotein that is often used as a biomarker for stem cells and cell stemness. However, it is not clear what factors can directly induce the expression of Sca‐1/Ly6A/E in T lymphocytes in vivo, and if induction of Sca‐1 is associated with T cell stemness. In this study, we show that interleukin‐27 (IL‐27), a member of the IL‐12 family of cytokines, directly induces Sca‐1 expression in T cells in vivo . We found that mice‐deficient for IL‐27 (either P28 or EBI3) or its signalling (IL‐27R α ) had profound reduction of Sca‐1 expression in naive (CD62L +  CD44 − ), memory (CD62L +  CD44 + ) and effector (CD62L −  CD44 + ) T cells. In contrast, in vivo delivery of IL‐27 using adeno‐associated viral vectors strongly induced the expression of Sca‐1 in naive and memory/effector T‐cell populations in an IL‐27 receptor‐ or signal transducer and activator of transcription 1‐dependent manner. Interestingly, IL‐27‐induced Sca‐1 + T cells do not express or up‐regulate classic stem cell‐associated genes such as Nanog, Oct4, Sox2 and Ctnnb1 . However, IL‐27‐induced Sca‐1 + T cells had increased expression of effector/memory‐associated transcription factor T‐bet, Eomes and Blimp1 . Hence, IL‐27 signalling directly induces the expression of Sca‐1/Ly6A/E expression in T cells. Direct expansion of Sca‐1 +  CD62L +  CD44 − T memory stem cells may explain why IL‐27 enhances T‐cell memory. Abstract : Interleukin‐27 signalling induces the expression of stem cell antigen‐1 in mature T lymphocytes in vivo, which leads to the expansion of the T memory stem cell population.